Pemanfaatan Platform Pemrograman Daring Dalam Pembelajaran Statistika Dan Probabilitas - Alven Natalius Sarumaha; Angel Dwi Artatika Sarumaha (CV. SINAR HOWUHOWU, 2024)
This study aims to evaluate the effectiveness of online programming platforms in teaching probability and statistics. The research employs a mixed-method design that combines quantitative and qualitative approaches. The study involves 60 students divided into two groups: the experimental group, which used platforms such as Python and RStudio, and the control group, which followed conventional teaching methods. The findings indicate that the experimental group experienced significantly greater learning outcomes compared to the control group. Additionally, the online platforms facilitated students' understanding of concepts through data visualization and interactive simulations, as well as improved their independent learning skills. However, challenges such as limited digital literacy and technological access remain significant obstacles. The study recommends integrating digital literacy into the curriculum and providing infrastructure support to maximize the benefits of technology-based learning.